2023
DOI: 10.3390/ecologies4040043
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Ecologically Suitable Areas of Cotton Cultivation Using the MaxEnt Model in Xinjiang, China

Lingling Li,
Hongqi Wu,
Yimin Gao
et al.

Abstract: Cultivating cotton and sustaining its productivity are challenging in temperate arid regions around the globe. Exploring suitable cotton cultivation areas to improve productivity in such climatic regions is essential. Thus, this study explores the ecologically suitable areas for cotton cultivation using the MaxEnt model, having 375 distribution points of long-staple cotton and various factors, including 19 climatic factors, 2 terrain factors, and 6 soil factors in Xinjiang. The area under the curve (AUC) of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…With the warming climate, the heat resources in Xinjiang have improved, resulting in an increasing cultivated area for the most suitable cotton zone (variety: mid-maturity cotton) and the suitable cotton zone (variety: mid-early-maturity cotton), while the area for the unsuitable cotton zone (variety: extra-early-maturity cotton) has decreased. Similar conclusions were drawn by Li et al [23], who also noted a decreasing trend for the less suitable cotton zone (variety: early-maturity cotton) and the unsuitable cotton zone. The observed increase in the cultivated area for the suitable cotton zone and the decrease in the area for the less suitable cotton zone and unsuitable cotton zone in this study are consistent with the changes in cotton zoning reported by Mai et al [15].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…With the warming climate, the heat resources in Xinjiang have improved, resulting in an increasing cultivated area for the most suitable cotton zone (variety: mid-maturity cotton) and the suitable cotton zone (variety: mid-early-maturity cotton), while the area for the unsuitable cotton zone (variety: extra-early-maturity cotton) has decreased. Similar conclusions were drawn by Li et al [23], who also noted a decreasing trend for the less suitable cotton zone (variety: early-maturity cotton) and the unsuitable cotton zone. The observed increase in the cultivated area for the suitable cotton zone and the decrease in the area for the less suitable cotton zone and unsuitable cotton zone in this study are consistent with the changes in cotton zoning reported by Mai et al [15].…”
Section: Discussionsupporting
confidence: 88%
“…Recent studies have shown that because it is influenced by changes in heat resources, the area of suitable cotton regions in Xinjiang has gradually increased, while the areas of less suitable and unsuitable cotton regions have decreased. At the same time, the areas of mid-mature and early-mid-mature cotton regions in Southern Xinjiang have been continuously expanding, while the areas of early-ripening and unsuitable cotton regions have decreased [23][24][25]. However, in actual production, due to the complexity of cotton varieties, there are cases of unreasonable selection regarding the maturity of varieties and the blind expansion of planting areas in some regions, which have a significant impact on the quality and yield of cotton [21,22,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential distribution modeling is a tool that has been used in ecology and biogeography for several years, in different taxonomic groups (Abdelaal et al, 2019;Jiménez et al, 2023;Li et al, 2023;Martínez-Méndez et al, 2016;Murillo-Pérez et al, 2022;Yun et al, 2022). This tool has been of great importance in the development of scientific strategies in the conservation of species or habitats (Austin, 2002;Beaumont et al, 2005;Espejo-Serna & López-Ferrari, 2018;López-Sandoval et al, 2015;Martínez-Méndez et al, 2016;Palma-Ordaz & Delgadillo Rodríguez, 2014;Rodríguez & López-Toledo, 2016;Soberón, 2010;Solís-Montero et al, 2022;Suárez-Mota et al, 2022;Villaseñor, 2018;Ye et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous studies on cotton cultivation in terms of its environmental impact (the use of pesticides, water consumption, and soil degradation), agronomic approaches, the phenological and physiological aspects of cotton growth and development, cotton cultivation during climate change, sustainable cotton production and organic cotton, the effects of air pollution on cotton fabric, cotton breeding and genetics, cotton yield and quality, the utilization of cotton, the cotton market, etc. [26,29,[33][34][35][36][37]. However, no published studies were found on the effects of technogenic air pollution on the biochemical composition of cotton grown in the immediate vicinity of a nitrogen-phosphate fertilizer factory.…”
Section: Introductionmentioning
confidence: 99%